Navigating Indonesia’s Digital Marketplace: An ARAS Approach for MSME Growth - I'tishom Al Khoiry (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to Indonesia's economy, driving growth and job creation. However, they face challenges like limited market access and inadequate digital skills, which hinder their competitiveness. Selecting the right marketplace is essential for MSMEs to enhance their presence and optimize operations. The Additive Ratio Assessment (ARAS) method provides a structured approach for evaluating marketplace options based on criteria such as operational costs, user-friendliness, features, customer support, and transaction security. By applying the ARAS method, MSMEs can identify platforms that best meet their needs while maximizing overall value. This evaluation offers clear guidance for MSMEs in choosing marketplaces that foster growth and sustainability in the digital economy. Ultimately, ARAS enhances decision-making for Indonesian MSMEs, enabling them to succeed in an increasingly competitive digital landscape.